Lower Tropospheric Response to Local Sea Surface Temperature Anomalies: A Numerical Study in the EUREC4 ${ extEUREC}^{4}$A Region - M. Borgnino; F. Desbiolles; A. N. Meroni; C. Pasquero (Geophysical Research Letters)
Abstract Ocean and atmosphere exchange energy and mass at their interface at a rate that depends on the dynamical and thermodynamical disequilibrium between water and air. In this work, using an atmospheric model forced by observed high resolution sea surface temperature (SST) fields, we show that the air‐sea disequilibrium is also maintained by atmospheric processes driven by fine scale SST patterns. The analysis focuses on north‐western tropical Atlantic and indicates that fine scale SST anomalies modulate the air column stability and the entrainment of dry air at boundary layer top. The main effect is a modification in near surface temperature and moisture content, which produces a negative response of relative humidity to local SST variability, resulting in a larger sensitivity of latent than sensible heat fluxes to local SST anomalies. Such sensitivities are quantified as 95% and 70% of fluxes upper bound, estimated with local atmospheric properties uncorrelated with SST anomalies.